The results of Manila - Reiner Morbach (Intereconomics, 1979)
The proceedings at UNCTAD V and its results have come in for much harsh public criticism in the world. In view of its modest results it must be asked whether future world trade conferences cannot be rendered more effective.
Keywords: 330; Unctad V